Makna Kebahagiaan dalam Lafadz al-Farah Menurut Tafsir as-Sa’di - Santoso, Budi; Nasrulloh, Nasrulloh (Lembaga Yasin AlSys, 2024)
This study examines the concept of happiness as expressed through the term al-farah in the Qur'an, as interpreted by Abdurrahman bin Nashir As-Sa'di in his work Tafsir As-Sa'di or Taysir al-Karim ar-Rahman fi Tafsir Kalam al-Mannan. The term al-farah appears in various contexts within the Qur'an, such as in QS. Yunus: 58, which highlights praiseworthy happiness, and QS. Al-Qasas: 76, which illustrates blameworthy joy. The research aims to analyze and describe As-Sa'di's interpretation of both positive and negative aspects of happiness and its implications for human life. According to As-Sa'di, commendable happiness stems from gratitude, obedience to Allah, and actions that yield benefits in both worldly and spiritual dimensions. On the other hand, negative happiness arises from arrogance, heedlessness, and straying from righteousness, as reflected in the story of Qarun. Using a descriptive qualitative method and thematic interpretation, this study draws on Tafsir As-Sa'di as the primary source, supplemented by secondary materials, including other tafsir works, Islamic literature, and scholarly articles. The findings suggest that understanding al-farah through As-Sa'di’s perspective can help individuals critically evaluate their sources of happiness, distinguishing between those that are beneficial and those that are harmful. This study highlights the importance of exploring the concept of happiness from an Islamic viewpoint and demonstrates how classical exegesis can provide guidance for navigating contemporary challenges and fostering meaningful joy in daily life.